Answer:
a). true
b). true
Explanation:
a).
Given : If a = 5, then ac = 5c
Let c be any constant.
a = 5 (given)
Therefore, ac = 5c
Here a is given a constant value (5), also let assume c to be a constant. So when we multiply each term we will get a constant value of 5c. The ratio does not change.
Hence proved.
b).
Given : If ac = 5c, then a = 5
Let c be any constant
It is given, a = 5
Therefore, ac = 5c
Here the product of two terms is given as 5c, where c is assume to be a constant. Then as a product rule, the value of a will be 5. The ratio will not change.
Hence proved.